Sound Radiation Characteristics of Acoustically Thick Composite Cylinders and Their Experimental Verification - S. JOSEPHINE KELVINA FLORENCE; K. RENJI (Archives of Acoustics, 2021)
Cylindrical shells made of composite material form one of the major structural parts in aerospace structures. Many of them are acoustically thick, in which the ring frequencies are much higher than their critical frequencies. In this work, sound radiation behaviour of acoustically thick composite cylinders is presented. Based on the structural and acoustic wave number diagrams, the modal average radiation resistances in the frequency band of interest are theoretically determined. The structural wavenumbers are determined considering transverse shear deformation. The results show lesser sound radiation between the critical and ring frequencies, and significant sound radiation near the ring frequency and beyond. In the absence of the present results the radiation efficiency is considered to be unity at all frequencies beyond the critical frequency, including near the ring frequency. The radiation resistances of the same cylinder are determined experimentally and they are in very good agreement with the theoretical estimates. As part of this investigation, an expression for determining the ring frequency of composite cylinder is also presented.